Product innovation and market and the bakery industry: experience from SMEs in Cali, Colombia, 2018 (National Administration Journal, 2021)
This research focuses on product innovation and marketing method for the bakery industry, where most of the companies may create gradual innovations, both in terms of marketing and products. This research of a qualitative type involves 36 differentSMEs that were studied by means of interviews, whose content was codified and analyzed. As a result, three elements were found: A) product innovation is linked to the geographical context according to the city socio-economic characteristics and climate changes; B) the bakery industry promotes marketing innovation, particularly distribution, while developing vertical integration strategies to reach geographical places where a more expensive outlet may be set up; C) innovations are rather created by the bakers than by the owners, which has implications for the company´s growth.
Keywords: Bakery industry; innovation; marketing